Performance Evaluation of Novel Eco-Materials Composed of Millet Husks, Rice Husks, and Polystyrene - Amadji, Paul Damien; Chabi, Edem; DOKO, Sanni; Houndedji, Céphas; Olodo, E.T. Emmanuel (My University, 2023)
Managing agricultural waste and expanded polystyrene (EPS) poses significant environmental and economic challenges. This study aims to create composites from millet husks, rice husks, and recycled EPS, using a manufacturing method that involves dissolving the polystyrene in a solvent followed by cold pressing. Various particle sizes and two binder dosages were investigated to assess their influence on the physico-mechanical properties of the composites. The mechanical properties obtained range from 2.54 to 4.47 MPa for the Modulus of Rupture (MOR) and from 686 to 1400 MPa for the Modulus of Elasticity in Bending (MOE). The results indicate that these composites have potential for applications in the construction sector, particularly for wood structures and interior decoration. Moreover, surface treatments could enhance their durability and mechanical properties. This research contributes to the valorization of agricultural and plastic waste as eco-friendly and economical construction materials.
Keywords: Bio-Based Composites; Millet Husk; Rice Husk; Expanded Polystyrene; Waste; Valorization; Sustainable Construction